Investigating the Risk Factors for Non Typhoidal Salmonella in Pediatric Populations: A Systematic Review - Widiyanto, Aris; Halimah, Trisakti; Mubarok, Ahmad Syauqi; Anasulfalah, Hakim; Atmojo, Joko Tri; Hanif, Ihsan (Global Health Science Group, 2024)
The risk factors for non-typhoidal Salmonella infections in pediatric populations are not fully understood, but this remains a critical area of study for improving child health. The aim of this review is to systematically analyze the available literature about the risk factors of non typhoidal salmonella among pediatric populations. The risk factors for non-typhoidal Salmonella infections in children were examined in all papers published between 2019 and 2024 using a systematic review of the literature using PRISMA criteria. Google Scholar, PubMed, and ProQuest are the three electronic databases that the writers searched. The query